Charitable giving in the German welfare state: Fiscal incentives and crowding out - Timm Bönke; Nima Massarrat-Mashhadi; Christian Sielaff (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
Governmental activities in welfare states influence private charitable giving predominantly in two ways: (1) government spending on the provision of public goods may cause crowding out of private charitable contributions; and (2) tax incentives may boost private charitable giving. For a rich sample of German income tax returns, we estimate elasticities of charitable giving regarding tax incentives, income and governmental spending. Using censored quantile regression, we are able to derive results for different points of the underlying distribution of charitable giving. Assuming a world with impure altruism (Andreoni 1990), we find evidence for impurely altruistic giving behaviour. Taking crowding out into account, tax deductibility of charitable giving suffices to foster private giving to offset foregone tax revenues.
Keywords: C31; H31; H53; 330; charitable giving; crowding out; price and income elasticity; censored quantile regression; income tax return data; Spende; Crowding out; Sozialtransfer; Steuerbegünstigung; Einkommenselastizität; Schätzung; Deutschland